Assessment of Patient Safety Culture in Midwives - Cansever, Sabahat Moralılar; Soğukpınar, Neriman (Eximia, 2024)
Although there may be different definitions in national and international literature, patient safety, in general terms, encompasses all the precautions taken by healthcare professionals in healthcare institutions to prevent harm to individuals as a result of care delivery. It is an indispensable component of quality healthcare services. Patient safety, crucial in all healthcare services, becomes even more significant during the pivotal period of pregnancy, which is a physiological process but also involves a delicate balance between health and illness. Therefore, it is expected that midwives working in the delivery room, in particular, handle patient safety with utmost care. In recent years, with the increase in studies related to the culture of patient safety, the quality, satisfaction, and safety of care provided by midwives have also become subjects of investigation. This thesis aims to assess the levels of patient safety culture perception among midwives working in the delivery room, as well as to evaluate their opinions regarding patient safety and identify the behaviors influencing these opinions. The population of the study consists of midwives working in the delivery rooms of Muş and Bitlis provinces. The sample selection was not applied; all midwives who wished to participate in the study were included. Data analysis was conducted using the computer-assisted SPSS 22.0 software package. Percentage distributions were used in statistical evaluation, and for group comparisons, the significance was determined by the "Chi-square (X2) test" for categorical variables, the "t-test" for comparing means between two groups, and the "one-way ANOVA test" for evaluating the significance of differences among more than two group means. The level of statistical significance was accepted as p< 0.05 for all tests. Midwives’ perceptions of patient safety culture were rated as moderate with 57%, and their patient safety ratings were determined to be "very good" with 44.4%. Within the scope of the hospital survey, among the 12 sub-areas of patient safety culture, "teamwork within units" had the highest positive response rate at 79.7%, while "non-punitive response to error" stood out with the lowest positive response percentage at 27.4%. The highest percentage of positive responses in the hospital survey regarding patient safety culture was determined to belong to the statement ’We work together as a team when there is a lot of work that needs to be done urgently, with 85.6%. The lowest percentage of positive responses was for the statement ’We work in crisis mode when there is a lot of work to be done and it needs to be done very quickly,’ which was 12.2%." In the conducted comparisons, a significant relationship was found between midwives’ working province, age groups, marital status, duration of employment in the institution, duration of work in the unit, professional experience, weekly working hours, and employment status parameters with the percentages of positive responses given to the sub-areas of the hospital survey on patient safety culture. When evaluating patient safety practices in the delivery room, factors affecting working conditions, adequacy of staff numbers, and patient safety should also be taken into consideration. In order for patient safety practices to be carried out comprehensively, regular training, involvement of midwives in the process, and active participation are required.